The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1074/jbc.m115.690396
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Covalent Flavin Assembly Factor to the Flavoprotein Subunit of Complex II

Abstract: Escherichia coli harbors two highly conserved homologs of the essential mitochondrial respiratory complex II (succinate: ubiquinone oxidoreductase). Aerobically the bacterium synthesizes succinate:quinone reductase as part of its respiratory chain, whereas under microaerophilic conditions, the quinol: fumarate reductase can be utilized. All complex II enzymes harbor a covalently bound FAD co-factor that is essential for their ability to oxidize succinate. In eukaryotes and many bacteria, assembly of the covale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 61 publications
3
41
2
Order By: Relevance
“…The flavoproteins were constructed with an N-terminal His tag. Previous work showed that a His tag does not interfere with covalent flavinylation of the proteins (27,35). This indicates that the proteins are folded correctly for interaction with the SdhE chaperone and that the His tag does not affect active site preorganization for self-catalytic FAD attachment (9,11,25,27,35).…”
Section: Characterization Of the Flavoproteinsmentioning
confidence: 94%
See 4 more Smart Citations
“…The flavoproteins were constructed with an N-terminal His tag. Previous work showed that a His tag does not interfere with covalent flavinylation of the proteins (27,35). This indicates that the proteins are folded correctly for interaction with the SdhE chaperone and that the His tag does not affect active site preorganization for self-catalytic FAD attachment (9,11,25,27,35).…”
Section: Characterization Of the Flavoproteinsmentioning
confidence: 94%
“…One notable difference between the bacterial and mammalian proteins was in their response to their covalent FAD assembly factors. In bacteria, SdhE readily dissociates from either SdhA or FrdA once the covalent FAD linkage has formed (35,63,64). By contrast, SDHAF2 binds very tightly to hSDHA, and mild chaotropic agents were needed to dissociate the tightly bound complex.…”
Section: Complex II Flavoprotein Catalysismentioning
confidence: 99%
See 3 more Smart Citations